Drawn Together Through Group Art Therapy: Intervention Responses of Adults With a Traumatic Brain Injury - Briks, Alan L.; Wiebe, Monica L.; Hirst, Sandra P.; Freeman-Cruz, E. Aiofe; Le Navenec, Carole-Lynne M.; Groeneweg, Gerrit (Canadian Journal of Counselling and Psychotherapy, 2020)
The authors explored the experiences of adults living with a traumatic brain injury (TBI) in group art therapy. Integral to this study was a replicable methodology, including an original group art therapy treatment protocol for research that may be useful for practice-based applications. The treatment protocol consisted of a selected series of therapeutic art exercises for a short-term, 12-session art therapy course of treatment. Thirteen adults living with a TBI participated in the study, divided into two treatment groups comprised of six and seven adults (four female, nine male), respectively. Several quantitative measures and assessment tools were chosen to rate pre-therapy and post-therapy differences in self-esteem, coping, cognitive capacity, and affect. These included the Neurobehavioral Cognitive Status Examination (or Cognistat), the Coopersmith Self-Esteem Inventory (adult form), Rosenberg’s Self Esteem Scale, the COPE Inventory, and the Affect Rating Scale. The study included a pre-intervention interview, the Diagnostic Drawing Series (DDS), a comparative analysis of formal characteristics of the artwork, student observation notes, commentary on select imagery illustrating therapeutic transformations within the treatment process, and a satisfaction survey. Analyses of the quantitative data revealed a significant reduction in anxiety with positive clinical trends noted in domains of affect, cognitive functioning, and coping styles. The authors concluded that the study should be replicated with additional variables included.